Spectrophotometric Determination of Trace Amount of Oxalic Acid Based on Zirconium(IV)-(DBM-Arsenazo)- Oxalic Acid System - ZHAI, QING-ZHOU (Asian Journal of Chemistry, 2010)
In hydrochloric acid medium (0.2 mol L-1), zirconium(IV) and DBM-arsenazo (DBM-ASA) form a blue-green complex with a 1 : 1 mole ratio. The addition of oxalic acid can quantitatively replace the DBM-arsenazo in the complex, which makes the coloured solution with enhance absorbance. At 520 nm, the concentration of oxalic acid is proportional to the increase of absorbance. Beer's law is obeyed over the concentration range of oxalic acid 1.0 × 10-5 - 3.0 × 10-4 mol L-1 with a correlation coefficient of 0.9968. The apparent molar absorptivity of the method is ε520 nm = 1.85 × 103 L mol-1 cm-1. The detection limit of the method for oxalic acid is 0.549 μg/mL. The effect of fifty-eight diverse substances on the determination of oxalic acid was examined. The method has good selectivity. It was directly applied to the determination of trace amount of oxalic acid in urine samples with satisfactory results.